2022
DOI: 10.1097/cm9.0000000000001948
|View full text |Cite
|
Sign up to set email alerts
|

Risk of tuberculosis in patients with rheumatoid arthritis treated with biological and targeted drugs: meta-analysis of randomized clinical trials

Abstract: Background:Concerns exist regarding the potential development of tuberculosis in patients with rheumatoid arthritis (RA) treated with biological and targeted drugs. We assessed systematically whether biological therapy increased the risk of tuberculosis in patients with RA by meta-analysis of randomized controlled trials (RCTs).Methods:A systematic literature search was conducted in PubMed, Embase, the Cochrane Library, and China Biology Medicine disc for RCTs evaluating biological therapy in patients with RA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Screening for latent TB before starting bDMARDs is included in screening programmes of most national and international rheumatology associations, while the same applies for tsDMARDs, although there is less evidence 27–32. On the other hand, there is some evidence that patients with AIIRD under treatment with csDMARDs and/or glucocorticoids have also increased risk for latent TB reactivation 29 33–37.…”
Section: Resultsmentioning
confidence: 99%
“…Screening for latent TB before starting bDMARDs is included in screening programmes of most national and international rheumatology associations, while the same applies for tsDMARDs, although there is less evidence 27–32. On the other hand, there is some evidence that patients with AIIRD under treatment with csDMARDs and/or glucocorticoids have also increased risk for latent TB reactivation 29 33–37.…”
Section: Resultsmentioning
confidence: 99%
“…Amony the 30 patients of LTBI, only 1 patient who refused LTBI prophylaxis treatment received tofacitinib treatment and reexamination of chest CT showed no obvious changes after 6 months. Despite the disease tends for AA to be prevalent in younger patients, the data that observed in larger, long-term studies of patients with rheumatoid arthritis strongly suggest a link between activation of tuberculosis and JAKi ( 18 , 19 ). In additional, our data showed that the proportion of tuberculosis infections detected among patients over 40 years is 43%, which decreased to 11% in the 18–40 age group.…”
Section: Discussionmentioning
confidence: 99%
“…Other conditions increase the risk of progression from infection to disease. These include silicosis (RR 4-30) [115,116], kidney failure (RR 10-25) [117,118], rheumatoid arthritis (RR 2-16) [111] and cancer (RR 2-40) [119][120][121]. In each of the conditions, the immune system is affected by the required treatment, making the patient less capable of self containing M. tuberculosis infection.…”
Section: Other Risk Factorsmentioning
confidence: 99%